Regiões pluviométricas e saúde no Rio Grande do Norte - Pollyanne Evangelista Da Silva; Lara De Melo Barbosa Andrade; Jean Souza Dos Reis (Confins)
Rainfall surplus and deficits, observed through the occurrence of severe storms and draughts, amplify the impact of poverty on the population of the Northeast Brazil, where the Rio Grande do Norte state is located. One of the consequences of these events is the potential adverse impact on public health, with the increased incidence of endemic diseases. The objective of this study is to identify areas that are most susceptible to climate-dependent diseases, considering homogeneous precipitation regions in the State of Rio Grande do Norte. Health data used in the study were obtained from the Ministry of Health, made available on the SUS Hospital Information System (SIH/SUS) website, of the DATASUS platform. Precipitation data were obtained by means of estimates processed by a MERGE method in the period of 2000 to 2016. Because of the high climate variability in Rio Grande do Norte, homogeneous precipitation regions were defined within the State. Cluster analysis was carried out for the determination of these regions, considering accumulated rainfall data in each municipality of the State, the Euclidean distance and Ward's method criterion. An analysis of variance (ANOVA) was also carried out in order to verify the influence of precipitation on the rates of hospitalization caused by climate-dependent diseases, according to the homogeneous precipitation regions. Four distinct clusters (region 1, region 2, region 3 and region 4) were identified. It was observed that the main causes of hospitalization are respiratory diseases followed by infectious and parasitic diseases. Considering the homogeneous regions, Regions 1 and 2 showed the highest hospitalization rates for infectious and parasitic diseases and respiratory diseases. However, Region 1 has low rainfall rates while Region 2 presents high precipitation volumes. Results also show the influence of climate in disease groups with relatable causes such as infectious and parasitic diseases, respiratory, circulatory system and digestive diseases.